UPAYA TENAGA PENDIDIK DALAM MENINGKATKAN MINAT BELAJAR WARGA BELAJAR - Rosi; Danial, Adang; Novitasari, Nastiti (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2023)
The interest of students in the kejar paket C program is considered low, due to various factors such as the lack of educators because the Pkbm Sabilul Huda educators are dual positions, the location is quite far between the institution and the residence of the students, the lack of attendance of the students as evidenced. This study aims to determine what efforts are made by educators in increasing the interest of learning citizens learning package C. The method used in this study is a qualitative method using a descriptive approach. The results of this study are that there are several efforts made by educators, namely 1) providing motivation, people learn more enthusiasm and foster a sense of interest in learning. 2) convey the purpose of learning, learning citizens can arouse the desire to know the implications of learning. 3) learning methods, can provide influence and better understand the material of learning to citizens. 4) using Learning media, residents learn not saturated and not sleepy. 5) give an assessment, to increase understanding. 6) giving praise, fostering the spirit and motivation of citizens to learn. Conclusion from the results of this study that the efforts of educators in increasing interest in learning always provide enthusiasm, encouragement, interest in learning citizens in following the learning.